Cu-co-la / ssz-13 oxygen vacancy catalyst and preparation method and application thereof

CN122999265APending Publication Date: 2026-10-30PUYANG HONGYE HI-TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611303669.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]然而,现有非贵金属催化剂在糠醛一步加氢制2-MTHF体系中仍存在明显技术短板:目标产物2-MTHF选择性难以稳定维持在97%以上,且催化剂长周期运行稳定性普遍不足500h,严重制约了工业化推广应用

Benefits of technology

1、通过选用Cu(NO3)2·3H2O、Co(NO3)2·6H2O和La(NO3)3·6H2O作为金属源,搭配柠檬酸、草酸、酒石酸或乙二胺四乙酸作为络合剂,且严格控制金属离子总摩尔数与络合剂的摩尔比为1:1.0~1.5,同时通过稀氨水或稀硝酸将pH精准调节至4.2~4.5,可形成稳定的金属络合体系,有效避免金属离子提前沉淀,确保三种金属离子在浸渍液中均匀分散,为后续催化剂活性位点的均匀分布奠定基础;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a Cu-Co-La / SSZ-13 oxygen vacancy catalyst and a preparation method and application thereof. The preparation method comprises the following steps: dissolving copper, cobalt and lanthanum nitrate in deionized water, adding a complexing agent and adjusting pH to 4.2-4.5 to obtain an impregnation solution; mixing the impregnation solution and a pretreated SSZ-13 molecular sieve carrier according to a liquid-solid ratio of 1:1.7-1.9, vacuum impregnating, standing and aging, drying, pre-calcining, reducing treatment and screening to obtain the Cu-Co-La / SSZ-13 oxygen vacancy catalyst. The Cu-Co-La / SSZ-13 oxygen vacancy catalyst takes the SSZ-13 molecular sieve with a silicon-aluminum ratio of 20-40 as a carrier, and loads Cu, Co and La, and the mass fractions of the three are 6.0-7.5wt%, 2.5-3.5wt% and 1.0-1.5wt% respectively based on the total mass of the catalyst, and the oxygen vacancy concentration is 1.8-2.2mmol / g. The catalyst preparation method is simple, has high specific surface area and pore volume, and when applied to a reaction of preparing 2-methyltetrahydrofuran from furfural through one-step hydrogenation, the catalyst can effectively inhibit a side reaction and improve the selectivity of a target product and the stability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst materials and biomass conversion technology, and more specifically to a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, its preparation method, and its application. Background Technology

[0002] 2-Methyltetrahydrofuran (2-MTHF) is a high-value-added bio-based platform chemical that can be widely used as a high-performance biofuel additive, a green organic solvent, and an important intermediate in the synthesis of pharmaceuticals and chemicals. Using furfural, a widely available and inexpensive biomass derivative, as a raw material, 2-MTHF can be directly synthesized via one-step selective hydrogenation. This method offers significant advantages such as high economic efficiency, a simple process flow, and renewable raw materials, and has become a key research direction in the field of biomass catalytic conversion.

[0003] The one-step hydrogenation of furfural to 2-MTHF is a complex reaction pathway, involving the selective hydrogenation of the carbonyl C=O bond in the furfural molecule to generate furfuryl alcohol, followed by further hydrogenation saturation via the furan ring C=C bond to obtain the target product 2-MTHF. This tandem reaction system exhibits multiple competing side reactions: furfuryl alcohol is prone to over-hydrogenation to tetrahydrofurfuryl alcohol; the furan ring is susceptible to ring-opening at acidic or metal active sites on the catalyst, generating C5 byproducts such as pentanone and pentanol; and molecular polymerization and coking can also occur during the reaction, leading to catalyst activity degradation and deactivation. Therefore, developing a dedicated catalyst with high catalytic activity, high product selectivity, and long-term operational stability is crucial for the industrial application of the one-step directed preparation of 2-MTHF from furfural.

[0004] Currently, catalysts used in this reaction are mainly divided into two categories: noble metal catalysts and non-noble metal catalysts. Noble metal catalysts are primarily Pd, Pt, and Ru-based systems. While they exhibit high initial catalytic activity, they suffer from drawbacks such as high raw material costs and scarce mineral resources. Furthermore, the selectivity for hydrogenation of the furan ring is difficult to precisely control, easily inducing ring-opening side reactions and reducing the yield of the target product. Non-noble metal catalysts are represented by Cu, Co, and Ni-based systems, with copper-based catalysts being particularly popular due to their intrinsic selectivity for hydrogenation of the carbonyl C=O bond. However, traditional copper-based catalysts generally suffer from low intrinsic activity, easy migration and sintering of the active metal at high temperatures, and insufficient ability to subsequently hydrogenate the furan ring. Existing technologies often employ the introduction of second metals such as Co and Zn to construct bimetallic synergistic systems, or utilize porous molecular sieve supports to optimize catalytic performance through pore confinement effects.

[0005] However, existing non-precious metal catalysts still have significant technical shortcomings in the one-step hydrogenation of furfural to 2-MTHF: the selectivity of the target product 2-MTHF is difficult to maintain stably above 97%, and the long-term operational stability of the catalysts is generally less than 500 hours, which seriously restricts their industrial application. The main reasons are as follows: First, traditional impregnation preparation processes easily lead to uneven dispersion of active metal components, and metal particles are prone to migration, agglomeration, and sintering during the reaction; second, the electronic structure of the active sites on the catalyst surface is poorly matched with the adsorption and activation characteristics of the reactants and intermediates, making it impossible to simultaneously achieve efficient catalytic carbonyl hydrogenation, suppress excessive adsorption of furan rings, and prevent ring-opening side reactions; third, there is a lack of precise control over defect sites such as oxygen vacancies on the catalyst surface, while oxygen vacancies play a key role in activating hydrogen, promoting hydrogen overflow, and regulating the adsorption configuration of reaction intermediates, and existing technologies cannot achieve synergistic matching and control between defect sites and active sites.

[0006] In view of this, the present invention is proposed. Summary of the Invention

[0007] The purpose of this invention is to address the problems mentioned in the background section by providing a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, its preparation method, and its application.

[0008] To achieve the above objectives, the present invention specifically adopts the following technical solution: A method for preparing a Cu-Co-La / SSZ-13 oxygen vacancy catalyst includes the following steps.

[0009] S1. Dissolve Cu(NO3)2·3H2O, Co(NO3)2·6H2O and La(NO3)3·6H2O in deionized water, add a complexing agent, and adjust the pH to 4.2~4.5 to obtain the impregnation solution; The total molar ratio of metal ions to complexing agent is 1:1.0~1.5; Furthermore, in step S1, the pH is adjusted to 4.2-4.5 using dilute ammonia or dilute nitric acid. On the one hand, this inhibits the hydrolysis reaction of metal ions (avoiding the formation of hydroxide precipitates such as Cu(OH)2 and Co(OH)2), ensuring the stability of the complex. On the other hand, it adjusts the degree of dissociation of the complexing agent, optimizes its coordination ability, and makes the complex more likely to interact with the active sites (such as silanol and aluminol) on the surface of the subsequent SSZ-13 molecular sieve support, thereby improving the loading efficiency.

[0010] Further, the complexing agent is citric acid, oxalic acid, tartaric acid, or ethylenediaminetetraacetic acid. It can react with Cu. 2+ Co 2+ La 3 +Stable polynuclear complexes are formed to achieve uniform dispersion of metal ions. Citric acid is the preferred complexing agent due to its strong complexing stability and lack of harmful residues after subsequent pyrolysis.

[0011] S2. The impregnation solution and the pretreated SSZ-13 molecular sieve carrier are mixed at a liquid-solid ratio of 1:1.7~1.9 and impregnated at -0.10~-0.08MPa for 4~6h. Then, the mixture is allowed to stand and age at room temperature for 2~3h to obtain the impregnated material. Under the synergistic effect of capillary action and negative pressure suction, the impregnation solution can quickly and fully penetrate into the microporous and mesoporous structures of SSZ-13, avoiding pore blockage. At the same time, it increases the contact area between the metal complex and the carrier surface, improving the loading capacity and loading uniformity.

[0012] Furthermore, the specific methods for pretreating the SSZ-13 molecular sieve support include: Calcination of the SSZ-13 molecular sieve support in air at 540–560 °C for 3–5 h thoroughly removes adsorbed moisture, organic impurities, and residual template agents from the support surface. Simultaneously, it generates more active hydroxyl groups (Si-OH, Al-OH) on the support surface, enhancing the interaction between the support and the metal complex. Then, the calcined SSZ-13 molecular sieve support is ultrasonically dispersed in a 0.08–0.12 mol / L nitric acid solution and activated at 50–70 °C for 1.5–2.5 h. Dilute nitric acid selectively etches impurity ions (such as Na+) from the support surface. + K + At the same time, the number of surface hydroxyl groups is further increased and the surface charge distribution of the carrier is regulated to enhance the adsorption capacity of the carrier for metal complexes. Ultrasonic dispersion can make the carrier uniformly dispersed in nitric acid solution to ensure uniform activation and avoid insufficient local activation. Then, it is filtered and washed until neutral, and then dried at 100~120℃ to remove the moisture in the carrier pores and ensure the integrity of the pore structure.

[0013] S3. After drying the impregnated material at 110~130℃, it is pre-calcined at 250~350℃, then reduced at 350~400℃ and cooled to room temperature to obtain the catalyst precursor. Further, in step S3, the impregnated material is dried at 110~130℃ for 5~7h, pre-calcined at 250~350℃ for 1~3h, then reduced at 370~390℃ for 4~8h, and then cooled to room temperature under an inert atmosphere to obtain the catalyst precursor.

[0014] Furthermore, under a nitrogen atmosphere, the temperature is increased to 250-350℃ at a rate of 5℃ / min to achieve slow and complete thermal decomposition of the complexing agent-metal complex. The nitrogen atmosphere prevents excessive oxidation of metal ions during calcination and also prevents the active sites on the support surface from being oxidized and destroyed by air. The slow heating rate of 5℃ / min avoids rapid temperature rise that could lead to rapid decomposition of the complex and the generation of large amounts of gas, causing blockage of the support channels or structural damage, while also ensuring more complete decomposition of the complex. This temperature range allows the complexing agent molecules to undergo oxidative decomposition, generating volatile products such as CO2 and H2O, thus completely removing complexing agent residues. Simultaneously, during thermal decomposition, the metal ions lose their coordination protection and react with oxygen in the air to generate metal oxides such as CuO, Co3O4, and La2O3. These metal oxides are uniformly dispersed on the surface and within the channels of the SSZ-13 molecular sieve support, forming a support-metal oxide composite structure.

[0015] In a 10% (v / v) H2 / N2 mixed atmosphere, the temperature is increased to 370–390 °C at a rate of 2 °C / min. H2 acts as a reducing agent to achieve moderate reduction of the metal oxides, while N2 acts as a protective gas to prevent oxidation of metal ions during reduction and to prevent damage to the support structure. The slow heating rate of 2 °C / min allows for gradual reduction of the metal oxides, preventing agglomeration of metal particles due to sudden temperature increases, and ensuring slow desorption of lattice oxygen to form stable oxygen vacancies. During the reduction process, H2 reacts with the metal oxides (CuO, Co3O4) to induce a reduction reaction, causing some high-valence metal ions (CuO, Co3O4) to undergo a reduction reaction. 2+ Co 3+ ) is reduced to low-valence metal ions (Cu) + Co 2+ This process is accompanied by the desorption of lattice oxygen. When oxygen atoms in a metal oxide lattice are reduced and desorbed, vacancies, or oxygen vacancies, are formed in the lattice positions that were originally occupied by oxygen atoms.

[0016] S4. The catalyst precursor was sieved to obtain Cu-Co-La / SSZ-13 oxygen vacancy catalyst.

[0017] Furthermore, the specific operation of the O2 pulse chemisorption method for determining oxygen vacancy concentration is as follows: The catalyst sample is pretreated at 300℃ in an H2 atmosphere for 1 h to completely reduce the metal oxide, then purged with He gas for 30 min to remove surface-adsorbed H2. After cooling to 50℃, O2 is pulsed into the sample, and the O2 consumption is detected using a chemisorption analyzer. The oxygen vacancy concentration is calculated based on the O2 consumption (μmol / g). The blank SSZ-13 molecular sieve support was tested under the same conditions, and its O2 consumption was <0.05 mmol / g, indicating that the interference of oxygen adsorption on the SSZ-13 molecular sieve support itself on the determination of oxygen vacancy concentration is negligible.

[0018] As an inventive concept with the same technical solution as above, the present invention also claims protection for a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, which is prepared by any of the methods described above for preparing Cu-Co-La / SSZ-13 oxygen vacancy catalyst, comprising an SSZ-13 molecular sieve support with a silicon-to-aluminum ratio of 20 to 40, wherein the SSZ-13 molecular sieve support is loaded with active components Cu, Co and La; Preferably, the silica-to-alumina ratio of the SSZ-13 molecular sieve support is 25. Under this silica-to-alumina ratio, the aluminum content in the support framework is moderate, which ensures sufficient cation exchange sites to anchor the active metal components, while avoiding excessive acidity sites caused by excessive aluminum content, thus preventing the furan ring-opening side reaction.

[0019] Based on the total mass of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst, the mass fractions of each component are: Cu 6.0~7.5wt%, Co 2.5~3.5wt%, and La 1.0~1.5wt%.

[0020] Furthermore, the Cu-Co-La / SSZ-13 oxygen vacancy catalyst has an oxygen vacancy concentration of 1.8~2.2 mmol / g and a specific surface area ≥420 m². 2 / g and pore volume ≥0.95cm 3 / g.

[0021] The SSZ-13 molecular sieve support has a CHA topological structure with micropore channel dimensions of 0.38 nm × 0.38 nm. Cu, Co, and La components are highly dispersed in the pores and surface of the SSZ-13 molecular sieve support, with La mainly enriched in the Cu-Co active phase interface region. Oxygen vacancies in the Cu-Co-La / SSZ-13 oxygen vacancy catalyst are primarily located in the Cu-O-Co interface region.

[0022] As an inventive concept with the same technical solution as above, this invention also claims protection for the application of a Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described above in the one-step hydrogenation of furfural to prepare 2-methyltetrahydrofuran.

[0023] The reaction was carried out at a temperature of 190–210℃, a reaction pressure of 1.2–1.5 MPa, and a furfural liquid hourly space velocity of 0.5–0.8 h⁻¹. -1Under the condition of a hydrogen to furfural molar ratio of 8-10:1, the furfural conversion rate is ≥98%, the selectivity of 2-methyltetrahydrofuran is ≥96%, and the yield of 2-methyltetrahydrofuran is ≥94%. When the oxygen vacancy concentration is in the range of 1.8-2.2 mmol / g, the yield of 2-methyltetrahydrofuran is positively correlated with the oxygen vacancy concentration; when the oxygen vacancy concentration is below 1.5 mmol / g or above 2.5 mmol / g, the catalytic performance decreases significantly, indicating that the oxygen vacancy concentration range specified in this application achieves the optimal balance between hydrogenation activity and selectivity.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By selecting Cu(NO3)2·3H2O, Co(NO3)2·6H2O and La(NO3)3·6H2O as metal sources, and combining them with citric acid, oxalic acid, tartaric acid or ethylenediaminetetraacetic acid as complexing agents, and strictly controlling the molar ratio of the total number of metal ions to the complexing agent to be 1:1.0~1.5, and precisely adjusting the pH to 4.2~4.5 with dilute ammonia or dilute nitric acid, a stable metal complex system can be formed, effectively avoiding the premature precipitation of metal ions, ensuring that the three metal ions are uniformly dispersed in the impregnation solution, and laying the foundation for the uniform distribution of the active sites of the catalyst in the future; 2. By pretreatment the SSZ-13 molecular sieve support with calcination in air at 540~560℃ for 3~5h, activation in 0.08~0.12mol / L nitric acid solution at 50~70℃ for 1.5~2.5h, filtration and washing until neutral, and drying at 100~120℃, impurities and residual organic matter on the support surface can be effectively removed. At the same time, the nitric acid activation increases the active groups on the support surface, enhancing the adsorption capacity of the support for Cu, Co, and La metal ions. Meanwhile, the pore structure advantage of the SSZ-13 molecular sieve support itself is preserved, providing favorable conditions for the formation of oxygen vacancies and the diffusion of reactants. Detailed Implementation

[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The materials and instruments used in the following embodiments are all commercially available.

[0026] In a first aspect, embodiments of the present invention provide a method for preparing a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, comprising the following steps: S1. Dissolve Cu(NO3)2·3H2O, Co(NO3)2·6H2O and La(NO3)3·6H2O in deionized water, add a complexing agent, and adjust the pH to 4.2~4.5 to obtain the impregnation solution; The total molar ratio of metal ions to complexing agent is 1:1.0~1.5; S2. Mix the impregnation solution and the pretreated SSZ-13 molecular sieve carrier at a liquid-solid ratio of 1:1.7~1.9 and impregnate at -0.10~-0.08MPa for 4~6h, then let it stand and age at room temperature for 2~3h to obtain the impregnated material. S3. After drying the impregnated material at 110~130℃, it is pre-calcined at 250~350℃, then reduced at 350~400℃ and cooled to room temperature to obtain the catalyst precursor. S4. The catalyst precursor was sieved to obtain Cu-Co-La / SSZ-13 oxygen vacancy catalyst.

[0027] Furthermore, in step S1, the pH is adjusted to 4.2-4.5 using dilute ammonia or dilute nitric acid.

[0028] Furthermore, the complexing agent is citric acid, oxalic acid, tartaric acid, or ethylenediaminetetraacetic acid.

[0029] Furthermore, the specific methods for pretreating the SSZ-13 molecular sieve support include: The SSZ-13 molecular sieve support was calcined in air at 540-560℃ for 3-5 hours. Then, the calcined SSZ-13 molecular sieve support was ultrasonically dispersed in a 0.08-0.12 mol / L nitric acid solution. After activation treatment at 50-70℃ for 1.5-2.5 hours, the solution was filtered, washed until neutral, and then dried at 100-120℃.

[0030] Further, in step S3, the impregnated material is dried at 110~130℃ for 5~7h, pre-calcined at 250~350℃ for 1~3h, then reduced at 370~390℃ for 4~8h, and then cooled to room temperature under an inert atmosphere to obtain the catalyst precursor.

[0031] Furthermore, under a nitrogen atmosphere, the temperature was increased to 250~350℃ at a rate of 5℃ / min; In a mixed atmosphere of H2 / N2 with a volume fraction of 10%, the temperature was increased to 370~390℃ at a rate of 2℃ / min.

[0032] Secondly, embodiments of the present invention provide a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, prepared by the method described above. The Cu-Co-La / SSZ-13 oxygen vacancy catalyst comprises an SSZ-13 molecular sieve support with a silica-to-alumina ratio of 20 to 40, wherein the SSZ-13 molecular sieve support is loaded with active components Cu, Co, and La; Based on the total mass of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst, the mass fractions of each component are: Cu 6.0~7.5wt%, Co 2.5~3.5wt%, and La 1.0~1.5wt%; the silica-alumina ratio of the SSZ-13 molecular sieve support is preferably 25.

[0033] Furthermore, the Cu-Co-La / SSZ-13 oxygen vacancy catalyst has an oxygen vacancy concentration of 1.8~2.2 mmol / g and a specific surface area ≥420 m². 2 / g and pore volume ≥0.95cm 3 / g.

[0034] Thirdly, embodiments of the present invention provide the application of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst prepared by the aforementioned method in the one-step hydrogenation of furfural to 2-methyltetrahydrofuran.

[0035] The reaction was carried out at a temperature of 190–210℃, a reaction pressure of 1.2–1.5 MPa, and a furfural liquid hourly space velocity of 0.5–0.8 h⁻¹. -1 Under the condition of a hydrogen to furfural molar ratio of 8~10:1, the furfural conversion rate is ≥98%, the selectivity of 2-methyltetrahydrofuran is ≥96%, and the yield of 2-methyltetrahydrofuran is ≥94%.

[0036] The present invention will be further described below with reference to specific embodiments and comparative examples.

[0037] Detection method: Catalyst component content: determined by inductively coupled plasma optical emission spectrometry (ICP-OES); Oxygen vacancy concentration: determined by O2 pulsed chemisorption method, the specific operation steps are as described above, the O2 consumption of blank SSZ-13 molecular sieve carrier is <0.05 mmol / g; Specific surface area and pore volume: determined using the Brunauer-Emmett-Teller (BET) method; Application performance evaluation: Furfural was hydrogenated in a high-pressure reactor in one step. After the reaction, the conversion rate of furfural, the selectivity of 2-methyltetrahydrofuran (2-methyltetrahydrofuran) and the yield were determined by gas chromatography (GC).

[0038] Example 1 1. Preparation steps: S1. Dissolve Cu(NO3)2·3H2O, Co(NO3)2·6H2O and La(NO3)3·6H2O in deionized water, add citric acid, and the total molar ratio of metal ions to citric acid is 1:1.2. Adjust the pH to 4.3 with dilute ammonia water to obtain the impregnation solution. S2. Calcine at 550℃ for 4 hours in air atmosphere, ultrasonically disperse in 0.1 mol / L nitric acid solution, activate at 60℃ for 2 hours, filter, wash until neutral, and dry at 110℃; mix the pretreated SSZ-13 molecular sieve carrier with the impregnation solution at a liquid-solid ratio of 1:1.8, impregnate at -0.09 MPa for 5 hours, and age at room temperature for 2.5 hours to obtain the impregnated material; S3. The impregnated material is dried at 120℃ for 6 hours, heated to 300℃ at 5℃ / min in a nitrogen atmosphere, and pre-calcined for 2 hours; then it is reduced to 380℃ at 2℃ / min in a mixed atmosphere of 10% H2 / N2 by volume for 6 hours, and cooled to room temperature under an inert atmosphere to obtain the catalyst precursor. S4. The catalyst precursor is sieved (20~40 mesh) to obtain Cu-Co-La / SSZ-13 oxygen vacancy catalyst.

[0039] 2. Catalyst performance test results: Component mass fraction: Cu 6.8 wt%, Co 3.0 wt%, La 1.2 wt%; Oxygen vacancy concentration: 2.0 mmol / g; specific surface area: 450 m² / g; pore volume: 1.02 cm³ / g.

[0040] 3. Application performance verification: Reaction conditions: reaction temperature 200℃, reaction pressure 1.3MPa, furfural liquid hourly space velocity 0.6h. -1 The molar ratio of hydrogen to furfural is 9:1; Reaction results: furfural conversion rate 98.5%, 2-methyltetrahydrofuran selectivity 97.2%, 2-methyltetrahydrofuran yield 95.7%.

[0041] Example 2 The difference between this embodiment and Embodiment 1 is that the pH in step S1 is 4.2, the molar ratio of metal ions to complexing agent is 1:1.0, and the remaining steps and process parameters remain unchanged.

[0042] Example 3 The difference between this embodiment and Embodiment 1 is that the liquid-to-solid ratio in step S2 is 1:1.7, the impregnation pressure is -0.10MPa, and the impregnation time is 6h.

[0043] Example 4 The difference between this embodiment and Embodiment 1 is that the reduction temperature in step S3 is 390℃ and the reduction time is 8h.

[0044] The following is a comparative analysis of Examples 1-4. The detection data of Examples 1-4 are shown in Table 1: Table 1. Detection data from Examples 1-4 As shown in Table 1 and Examples 1-4, compared to Example 1, Example 2, by lowering the pH to 4.2 and reducing the amount of complexing agent (metal ion to complexing agent molar ratio 1:1.0), resulted in a decrease in the catalyst's oxygen vacancy concentration, specific surface area, and pore volume, and a reduction in the 2-methyltetrahydrofuran yield to 92.3%. This indicates that a suitable pH (around 4.3) and complexing agent amount (around 1:1.2) can promote uniform dispersion of metal ions and improve the catalyst's structural performance. Example 3, by adjusting the liquid-to-solid ratio to 1:1.7, reducing the impregnation pressure to -0.10 MPa, and extending the impregnation time to 6 hours, improved the catalyst performance. The yield was slightly lower than that of Example 1 (2-methyltetrahydrofuran yield 94.1%), indicating that the combination of liquid-solid ratio 1:1.8, impregnation pressure -0.09 MPa, and impregnation time 5 h is more conducive to sufficient contact between the impregnation solution and the support, thus improving the loading effect. In Example 4, the reduction temperature was increased to 390 °C and the reduction time was extended to 8 h, which increased the oxygen vacancy concentration of the catalyst to 2.2 mmol / g and the pore volume to 1.05 cm³ / g, and the yield of 2-methyltetrahydrofuran reached 96.3%, which was better than that of Example 1. This shows that appropriately increasing the reduction temperature and extending the reduction time can increase the number of oxygen vacancies and optimize the catalytic activity.

[0045] Example 5 The difference between this embodiment and Example 1 is that the parameters for application performance verification are changed. In this embodiment, one hydrogenation reaction parameter is changed sequentially, while the remaining reaction conditions are the same as in Example 1.

[0046] The temperature of the first reaction was changed to 190℃, the pressure of the second reaction was changed to 1.5MPa, and the liquid hourly space velocity of the third reaction was changed to 0.8h. -1 The fourth time, the molar ratio of hydrogen to furfural was changed to 10:1.

[0047] The data from four tests in Example 5 are shown in Table 2: Table 2 Data from four tests Example 5 used the same batch of catalyst prepared in Example 1, without changing any preparation parameters. Only the key parameters of the furfural hydrogenation reaction (reaction temperature, reaction pressure, furfural liquid hourly space velocity, and hydrogen to furfural molar ratio) were adjusted. Only one parameter was changed each time, and the other application conditions were the same as those in Example 1.

[0048] As shown in Table 2 and Example 5, the four sets of parallel experimental data in Example 5 clearly demonstrate the influence of various hydrogenation reaction parameters on the yield of 2-methyltetrahydrofuran, and also verify the rationality of the application parameter range defined in this invention, as detailed below: When the reaction temperature dropped to 190°C (which is the lower limit of the range defined in this invention), the yield of 2-methyltetrahydrofuran dropped to 91.5%, which is lower than 95.7% in Example 1. This indicates that too low a temperature will lead to incomplete hydrogenation reaction, a decrease in reaction rate, and thus a reduction in the yield of the target product. When the reaction pressure was increased to 1.5 MPa (which is the upper limit of the range defined in this invention), the yield of 2-methyltetrahydrofuran reached 95.9%, which is basically the same as that in Example 1. This shows that within the defined pressure range, appropriately increasing the pressure will not significantly affect the yield and can ensure the stability of the reaction. When the liquid hourly space velocity increases to 0.8 h -1 When the yield of 2-methyltetrahydrofuran was at the upper limit of the scope of this invention, it dropped to 90.7%, which was lower than that of Example 1. This indicates that an excessively high liquid hourly space velocity would result in insufficient contact time between furfural and the catalyst, incomplete reaction, and reduced yield. When the molar ratio was increased to 10:1 (which is at the upper limit of the scope defined in this invention), the yield of 2-methyltetrahydrofuran reached 96.1%, which is slightly higher than that in Example 1. This indicates that appropriately increasing the amount of hydrogen can promote the forward hydrogenation reaction and improve the yield of the target product.

[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that only Cu is loaded, with a Cu mass fraction of 6.8 wt%, while the other preparation parameters remain unchanged.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that only citric acid is not added, while the other preparation parameters remain unchanged.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the SSZ-13 molecular sieve support is not calcined or activated with nitric acid, but is used directly for impregnation, while the other preparation parameters remain unchanged.

[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that only the reduction temperature in S3 is changed to 450°C, while the other preparation parameters remain unchanged.

[0053] The detection data for comparative examples 1-4 are shown in Table 3: Table 3 shows the detection data for comparative examples 1-4. As shown in Table 3, Example 1, and Comparative Example 1, Comparative Example 1 only removed Co and La loadings and retained Cu loadings. The oxygen vacancy concentration of the catalyst decreased from 2.0 mmol / g to 0.8 mmol / g, the specific surface area and pore volume decreased significantly, and the yield of 2-methyltetrahydrofuran decreased from 95.7% to 69.9%. This fully demonstrates that Cu-Co-La trimetallic synergistic loading is the key to improving the catalyst's structural performance and catalytic activity. In Comparative Example 2, without the addition of a complexing agent, the oxygen vacancy concentration of the catalyst decreased to 1.2 mmol / g, and the yield of 2-methyltetrahydrofuran decreased to 83.3%. This indicates that the addition of a complexing agent can promote the uniform dispersion of Cu, Co, and La metal ions on the SSZ-13 molecular sieve support, facilitate the formation of oxygen vacancies, and thus optimize the catalytic performance. In Comparative Example 3, the SSZ-13 molecular sieve support was used directly for impregnation without calcination and nitric acid activation pretreatment. The oxygen vacancy concentration of the catalyst was reduced to 1.4 mmol / g, and the yield of 2-methyltetrahydrofuran was 83.4%. This indicates that support pretreatment can effectively remove impurities on the support surface, increase active sites, promote metal ion loading and oxygen vacancy generation, and improve the overall performance of the catalyst. Comparative Example 4 increased the reduction temperature to 450℃, which exceeds the 350~400℃ range defined in this invention. The oxygen vacancy concentration of the catalyst decreased to 1.5 mmol / g, the specific surface area and pore volume decreased, and the yield of 2-methyltetrahydrofuran decreased to 79.2%. This proves that the reduction temperature range defined in this invention is reasonable. Excessive temperature will damage the catalyst structure, leading to a decrease in oxygen vacancy concentration and catalytic activity.

Claims

1. A method for preparing a Cu-Co-La / SSZ-13 oxygen vacancy catalyst, characterized in that, Includes the following steps: S1. Dissolve Cu(NO3)2·3H2O, Co(NO3)2·6H2O and La(NO3)3·6H2O in deionized water, add a complexing agent, and adjust the pH to 4.2~4.5 to obtain the impregnation solution; The total molar ratio of metal ions to complexing agent is 1:1.0~1.5; S2. Mix the impregnation solution and the pretreated SSZ-13 molecular sieve carrier at a liquid-solid ratio of 1:1.7~1.9 and impregnate at -0.10~-0.08MPa for 4~6h, then let it stand and age at room temperature for 2~3h to obtain the impregnated material. S3. After drying the impregnated material at 110~130℃, it is pre-calcined at 250~350℃, then reduced at 350~400℃ and cooled to room temperature to obtain the catalyst precursor. S4. The catalyst precursor was sieved to obtain Cu-Co-La / SSZ-13 oxygen vacancy catalyst.

2. The preparation method of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 1, characterized in that, In step S1, the pH is adjusted to 4.2-4.5 using dilute ammonia or dilute nitric acid.

3. The preparation method of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 1, characterized in that, The complexing agent is citric acid, oxalic acid, tartaric acid, or ethylenediaminetetraacetic acid.

4. The preparation method of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 1, characterized in that, Specific methods for pretreating SSZ-13 molecular sieve supports include: The SSZ-13 molecular sieve support was calcined in air at 540-560℃ for 3-5 hours. Then, the calcined SSZ-13 molecular sieve support was ultrasonically dispersed in a nitric acid solution with a concentration of 0.08-0.12 mol / L. After activation treatment at 50-70℃ for 1.5-2.5 hours, the solution was filtered, washed until neutral, and then dried at 100-120℃.

5. The preparation method of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 1, characterized in that, In step S3, the impregnated material is dried at 110~130℃ for 5~7h, pre-calcined at 250~350℃ for 1~3h, then reduced at 370~390℃ for 4~8h, and then cooled to room temperature under an inert atmosphere to obtain the catalyst precursor.

6. The preparation method of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 5, characterized in that, Under nitrogen atmosphere, the temperature is increased to 250~350℃ at a rate of 5℃ / min; In a mixed atmosphere of H2 / N2 with a volume fraction of 10%, the temperature was increased to 370~390℃ at a rate of 2℃ / min.

7. A Cu-Co-La / SSZ-13 oxygen vacancy catalyst, characterized in that, The Cu-Co-La / SSZ-13 oxygen vacancy catalyst prepared by any one of claims 1 to 6 includes an SSZ-13 molecular sieve support with a silicon-to-aluminum ratio of 20 to 40, wherein the SSZ-13 molecular sieve support is loaded with active components Cu, Co and La. Based on the total mass of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst, the mass fractions of each component are: Cu 6.0~7.5wt%, Co 2.5~3.5wt%, and La 1.0~1.5wt%.

8. The Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 7, characterized in that, The Cu-Co-La / SSZ-13 oxygen vacancy catalyst has an oxygen vacancy concentration of 1.8~2.2 mmol / g and a specific surface area ≥420 m². 2 / g and pore volume ≥0.95cm 3 / g.

9. The Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 7, characterized in that, The silicon-to-aluminum ratio of the SSZ-13 molecular sieve support is 25.

10. The application of the Cu-Co-La / SSZ-13 oxygen vacancy catalyst as described in claim 7 in the one-step hydrogenation of furfural to prepare 2-methyltetrahydrofuran; in, The reaction was carried out at a temperature of 190–210 °C, a pressure of 1.2–1.5 MPa, and a liquid hourly space velocity of 0.5–0.8 h⁻¹. -1 Under the condition of a hydrogen to furfural molar ratio of 8~10:1, the furfural conversion rate is ≥98%, the selectivity of 2-methyltetrahydrofuran is ≥96%, and the yield of 2-methyltetrahydrofuran is ≥94%.